Maclura tinctoria (L.) D. Don ex Steud. (Moraceae): a review of the advances in ethnobotanical knowledge, phytochemical composition, and pharmacological potential (2024)
ABSTRACT: Maclura tinctoria (Moraceae), commonly known as dinde, is a lactescent tree of significant economic importance with extensive ethnomedicinal and ethnobotanical applications. Among native populations in the Neotropics, dinde is used to address diverse forms of inflammatory arthritis, along with ailments stemming from viral, bacterial, or fungal origins. Its efficacy stands out notably in the treatment of conditions affecting the buccal cavity, respiratory tract, and venereal infections. These medicinal attributes have spurred investigations into their potential for developing nutraceuticals and pharmacological agents. Also, dinde has a commercial appeal intertwined with the remarkable qualities of its wood, which include the resistance to moisture and termites. This review consolidates information encompassing peer-reviewed articles from major scientific databases such as Science Direct, Scopus, Springer, PubMed, and Google Scholar. The review spans fifty-four phytocompounds, characterized by remarkable structural complexity and identified from the year 2000 onward. These compounds are categorized into favones, isoflavones, flavonols, flavonols, favanones, chalcones, and xanthones, where a significant portion exhibiting glycosylation or prenylation. Additionally, phenolic acids and condensed tannins contribute to the chemical diversity of this species. This comprehensive review offers updated insights into the potential bioactivity of chemical constituents identified in this plant, elucidating findings derived from different studies employing both in vitro and in vivo assays.